Pengaruh Media Pembelajaran Wordwall “Labelled Diagram” terhadap Hasil Belajar Siswa pada Materi Bersatu dalam Keberagaman Pembelajaran Pendidikan Pancasila - Ai Siti Gina Nur Agnia; Titin Rustini; Yayang Furi Furnamasari (Educatio, 2026)
This study aims to determine the effect of the Wordwall "labelled diagram" learning media on students' learning outcomes in the Unity in Diversity topic within Pancasila Education. The background of this research is the low student learning outcomes and the need for interactive media to enhance students' understanding. The method used was a quasi-experiment with a non-equivalent control group design. The subjects were 20 third-grade students from SDN Cilingga as the experimental class and 20 students from SDN Tugu 3 as the control class. The instrument used was a learning outcome test consisting of multiple-choice and short answer questions. The results showed an increase of 15.55 points in the experimental class. The paired sample t-test showed a significance value of < 0.001, and the independent sample t-test indicated a significant difference between the two groups (Sig. 0.012 < 0.05). Therefore, the wordwall "labelled diagram" media has a significant effect on improving student learning outcomes.